A Quantitative Study of Rhythm of Literal and Metrical Translations of Khayyam’s Rubaiyat Based on Grabe and Low’s Theory - Ferdowsi, Sima; Abolhasanizadeh, Vahideh (Iranian Journal of Translation Studies, 2015)
Poetry translation has always been the focus of attention within the field of literary translation. Therefore, various methods have been introduced for it. The present study tried to offer a quantitative comparison of literal and metrical strategies of poetry translation focusing on the rhythm of the language. To do so, 19 Persian quatrains of Khayyam were randomly chosen and compared with their English literal and metrical translations. Then a text grid has been made for each sentence in a way that the boundaries of each vowel were determined. Grabe and Low (2002) presented an empirical quantitative measure of rhythm one of whose factors is measuring vowel durational variability by nPVI. The durational variability of vowels was measured by nPVI. The results of comparing literal and metrical translations nPVI indicated that both of them were closer to English than Persian, and literal nPVI is less than that of metrical, but the difference is not significant. The findings of the study clearly revealed that both methods create a poem based on the rhythm system of the TL.